GAMBARAN SIBLING RIVALRY DAN DAMPAK PERILAKU ANAK PRASEKOLAH - Dini Kurnia Zarni; Herlina " "; Siti " Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Sibling rivalry is competition between sibling stoget love, affection and attention of one or both of their parents to get a confession or more and inflict the impact on the behavior. This research aim to know determine sibling rivalry and impact for  preschool children’s.Desain of research used deskripif analitik design with cross sectional. This research was conducted in TK Pertiwi Pekanbaru with 130 populations. Sample in this research througt 56 respondents that taken by using purposive sampling technique. Analysis in this research used univariate. The instrument in this research was observational sheet. The result  of this research represent the most children are 43 (76,8%) 6 years old, the most of children are male 33(58,%), the distance of the age with sister/brother on 5 years(age of sister/brother is 1 year) are 19 (33,9%). Prescool  Children’s with sibling rivarly are 35 (62,5%) and impact on behavior are 29 (51,8%). Conclusion of research result points out that impact of sibling rivalry  more a lot of gets positive character as child want to play and studying with its friend, often asks by friend and child want to share by environmentally its school. Suggested to oldster and family moring to notice child relationship with its brother in order not to happens impact of sibling rivalry  on child. Keywords                    : impact on behavior, preschool, sibling.